'It's a part of me and I'm a part of it': ecological thinking in contemporary Scottish folk music. Issue 3 (1st September 2020) - Hawitt, Rowan Bayliss
ABSTRACT: In recent years, Scottish folk musicians have increasingly referenced and incorporated Scottish topography, place and wildlife within their music, often positioning humans as inseparable from a wider natural-cultural ecosystem. This 'ecological thinking' both reflects and shapes issues of locality and place in Scottish music; tropes of (Scottish) folk music as 'close to nature' are variously demarcated or blurred in such thinking. In addition, these folk musicians use their music to present a critical perspective on explicitly environmental and political issues, addressing in particular the historical and current relationships between 'humans' and 'nature'. Drawing on semi-structured interviews with musicians and musical analysis, this article explores how two case study albums negotiate place, mythology and embedded human-nonhuman dyads with reference to the natural world. I argue that an ethics of solidarity and care underpins these musicians' output, exploring how music can enable a reflexive and often contradictory form of ecological thinking.